Implementation of The K-Nearest Neighbor Method to Determine The Quality of Export Import Swallow's Nest - Benny Johanes; Delpy Nisma Mendrofa; Oloan Sihombing (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
In this study discusses the quality of the feasibility of swallow's nests that are suitable for export, Based on the problem from the research, it discusses how to select export-worthy swallow's nests in order to maintain the confidence of buying from abroad. The method used in this research is the K-NN method which can determine the feasibility of applying for the rank of lecturer. The data that is processed is 100, the input criteria for bowl 4, broken 2, destroyed a 2, destroyed b 2. This system succeeded in displaying appropriate and inappropriate results for lecturer data that had been input into the data set.